The macro-and megabenthic fauna on the continental shelf of Prydz Bay, east Antarctica. (April 2022) - Mou, Jianfeng; Liu, Kun; Huang, Yaqin; He, Xuebao; Zhang, Shuyi; Wang, Jianjia; Lin, Junhui; Lin, Heshan; Liu, Wenhua
Abstract: Ten triangle trawls in Prydz Bay were collected from 97 m to 638 m. A total of 206 species of macro- and mega-benthos were identified, belonging to 9 phyla and 118 families, of which pycnogonids (41 species), gammarid amphipods (38 species) and echinoderms (36 species) were the most dominant groups. The species richness per station varied from 1 to 92. The abundance of macro- and mega-benthos (1 × 10 −3 -0.24 Ind./m 2 ) was low, compared to that in the southeastern Weddell Sea (131–1.28 × 10 3 Ind./m 2 ) and South Shetland waters (160–4.38 × 10 3 Ind./m 2 ). The results were similar to the Amundsen Sea abundances (1.10 × 10 −3 -0.40 Ind./m 2 ) at comparable depths and in the Antarctic deep sea. The macrobenthic community had 2 types, Sessile Suspension Feeders with Associated fauna - dominated by sponges (SSFA-SPO) and mobile deposit feeders, infauna and grazers - epifauna dominated (MOIN-EPI). The macrobenthic community in Prydz Bay showed a dispersed patchy distribution pattern which may result from the Antarctic water mass and iceberg scouring.